PEMILIHAN KEPALA DAERAH OLEH DEWAN PERWAKILAN RAKYAT DAERAH PASCA PUTUSAN MK NO. 85/PUU-XX/2022: Regional Head Elections by People’s Legislative Council after the Prevailing of Constitutional Court Decision No 85/PUU-XX/2022 - Baharuddin Riqiey (Constitution Journal, 2023)
The regional head election can be held in two models, namely direct election or election through People’s Legislative Council. Both are constitutional as stated in Constitutional Court Decision No. 97/PUU-XI/2013. However, after the prevailing of Constitutional Court Decision No. 85/PUU-XX/2022, which does not differentiate between general election and regional head election, then as one of the principles contained in Article 22E of the 1945 Constitution of the Republic of Indonesia, namely the principle of "direct" becomes a problem. Thus, the aim of the paper is to examine and analyze the true meaning of the phrase "elected democratically" in Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia, and the constitutionality of Regional Head Elections by People’s Legislative Council as well as who has the authority to decide disputes over the regional head elections. Legal research method with normative design was applied. The research findings indicate that the phrase "elected democratically" in Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia means that regional heads can be directly elected by the people or through People’s Legislative Council; but after the prevailing of Constitutional Court Decision No. 85/PUU-XX/2022, Regional Head Election through People’s Legislative Council is unconstitutional because it has been already included into the category of general election and must be carried out directly to the people as mandated in Article 22E of the 1945 Constitution of the Republic of Indonesia, and the Constitutional Court  has the authority to decide disputes over the elections. Keywords: Pilkada, DPRD, Constitutional Court. Mekanisme pemilihan kepala daerah dapat dilaksanakan dengan dua model, yaitu dapat dilakukan secara langsung oleh rakyat, dan dapat dilakukan oleh DPRD. Dua model tersebut merupakan dua model yang konstitusional sebagaimana halnya dalam Putusan MK No. 97/PUU-XI/2013. Akan tetapi setelah lahirnya Putusan MK No. 85/PUU-XX/2022, yang mana tidak lagi membedakan antara rezim Pemilu dengan rezim Pilkada, maka sebagai salah satu asas yang terdapat pada Pasal 22E UUD NRI 1945 yakni asas “langsung” maka hal ini menjadi persoalan. Dengan demikian tujuan dari penulisan ini adalah untuk mengkaji dan menganalisis makna sesungguhnya dari frasa “dipilih secara demokratis” dalam Pasal 18 ayat (4) UUD NRI 1945, serta konstitusionalitas Pemilihan Kepala Daerah oleh DPRD, dan siapa yang berwenang dalam memutus perselisihan hasil sengketa Pilkada. Metode yang digunakan adalah metode penelitian hukum dengan tipe penelitian normatif. Hasil penelitian ini menujukkan bahwa makna frasa “dipilih secara demokratis” dalam Pasal 18 ayat (4) UUD NRI 1945 dapat dipilih langsung oleh rakyat maupun juga dapat dipilih oleh DPRD akan tetapi pasca Putusan MK No. 85/PUU-XX/2022 Pemilihan Kepala Daerah oleh DPRD adalah inkonstitusional sebab Pilkada sudah masuk di dalam kategori rezim Pemilu dan harus dilakukan secara langsung oleh rakyat sebagaimana amanat dalam Pasal 22E UUD NRI 1945, dan yang berwenang dalam memutus perselisihan hasil sengketa Pilkada adalah MK. Kata Kunci : Pilkada, DPRD, Mahkamah Konstitusi